KRAS G12 isoforms exert influence over up-front treatments: A retrospective, multicenter, Italian analysis of the impact of first-line immune checkpoint inhibitors in an NSCLC real-life population - Fancelli, Sara; Caliman, Enrico; Mazzoni, Francesca; Paglialunga, Luca; Gatta Michelet, Marta Rita; Lavacchi, Daniele; Berardi, Rossana; Mentrasti, Giulia; Metro, Giulio; Birocchi, Ilaria; Delmonte, Angelo; Priano, Ilaria; et al. (Frontiers in Oncology, 2022)
Background: KRAS is commonly mutated in non-small cell lung cancer (NSCLC) however the prognostic and predictive impact of each G12 substitution has not been fully elucidated. The approval of specific G12C inhibitors has modified the idea of KRAS “undruggability”, and although the first-line standard consists of immune check-point inhibitors (ICIs) with or without chemotherapy, as suggested at ASCO 2022, the outcome in KRAS mutated population is still controversial. Methods: we retrospectively described the clinical and pathological characteristics of a homogeneous G12 mutated cohort of 219 patients treated in four Italian Oncologic Units. We evaluated the outcome (PFS at 18 months and OS at 30 months) of those treated with standard first line according to PD-L1 status focusing on differences across single mutations. Results: In the study population, 47.9% of patients harbor the KRAS G12C mutation, 20.5% G12V, 17.4% G12D and 8.2% G12A. Smoking was a common behavior of patients harboring transversions and transition mutations. PD-L1 expression does not show particular distribution in the case series, although we recorded a prevalence of PD-L1 <1% in G12V (51.4%) compared to G12A (26.7%). ICIs alone was the clinician choice in 32.7% and chemo-immune combinations in 17.3% patients. We described the independent prognostic role of young age (p=0.007), female gender (p=0.016) and an ICI-based regimen (p=0.034) regardless of mutations. Overall, our data confirm the worst prognostic value of G12V mutation apart from treatment choice unlike the other major mutations (C, D and A) that showed a favorable trend in PFS. Conclusions: KRAS G12 mutations confirm to have different characteristics and the outcome is influenced by ICI first-line regimen. This study provides valuable information for further analysis in the future.